Answer:
![x=-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/whlztoonow2sjij0bijxz0wnqgda4xeqq1.png)
Explanation:
By the negative exponent rule, you have that:
![((1)/(a))^n=a^(-n)](https://img.qammunity.org/2020/formulas/mathematics/high-school/wybo84ihxu6fclrnm0k4erx4f7d5cjtzg6.png)
By the exponents properties, you know that:
![(m^n)^l=m^((nl))](https://img.qammunity.org/2020/formulas/mathematics/high-school/d2gz0fpbml3sogdrjpv4ve7cd4qmvhsmew.png)
Therefore, you can rewrite the left side of the equation has following:
![((1)/(8))^(-(2x+7))=((1)/(32))^(3x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/38wcyfpynzejev9m7yf8cfkzt5x04o8ues.png)
Descompose 32 and 8 into its prime factors:
![32=2*2*2*2*2=2^5\\8=2*2*2=2^3](https://img.qammunity.org/2020/formulas/mathematics/high-school/ds0wv154l8jwxbhkarrpoy2jw5j742lccj.png)
Rewrite:
![((1)/(2^3))^(-(2x+7))=((1)/(2^5))^(3x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/m6bq55v9qrbcwr51u9k1mhz88oylr6p4vr.png)
Then:
![((1)/(2))^(-3(2x+7))=((1)/(2))^(5(3x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/furl3iqx5zgmhl8o5fdvbbdko4dg7rt23p.png)
As the base are equal, then:
![-3(2x+7)=5(3x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3f87v22nl4o1jgr416dk1b99ah7oj1o8z1.png)
Solve for x:
![-6x-21=15x\\-21=15x+6x\\-21=21x\\x=-1](https://img.qammunity.org/2020/formulas/mathematics/high-school/ns61sv66tjpocf57vfmnntsfxr6c6t98z8.png)